Basic themes of Chinese indigenous psychology - Václav Linkov (Psychology and its Contexts, 2019)
Indigenous psychologies study local phenomena through concepts and terminology native to people in the given culture in order to provide a deeper understanding of the local culture. Indigenous psychologies began to spread in 1970 s in various non-western countries. Chinese indigenous psychology began as a movement for liberating psychology in Chinese areas from western influences. In this text, we review the culturally specific themes studied by Chinese indigenous psychologists. One popular concept studied by many researchers is guanxi. Guanxi is a relationship between two people which is based on something that they have in common and which is maintained by the mutual exchange of favors. The possibility of receiving help is the main reason people seek to establish guanxi. Another concept is that of the “face”. Face represents evaluation of person’s behavior in a social situation. Chinese people are very concerned with saving face for themselves and their acquaintances. Face could be lost through the incorrect behavior of a person, and also through the misbehavior of a family member. It is better to lose face in the presence of strangers than in the presence of people who are close. Renqing is the will to help another person. If someone receives renqing, he or she should return it. It is hard to measure the value of a favor, so it can never be fully returned. Chinese people, therefore, do not like to receive renqing from someone. Yuan is destiny, which is responsible for relationships. A romantic relationship is considered to be based upon good or bad yuan. If the relationship does not go well, it is not the responsibility of partners or people who persuaded couple to start relationship (i.e., parents), but it is because of yuan. In this way, yuan helps to maintain social harmony. Filial piety (xiao) binds children to their parents. Children should respect their parents and their parents can influence their children’s decisions, including romantic-partner selection. Chinese parents enforce tight control of their children from early childhood. Zhong yong is the tendency to maintain a middle-of-the-road style of thinking and behavior. Everything should be perceived from many points of view and a decision should be not made too quickly. Extremes should be avoided. Suzhi is the quality of a person – moral characteristics, abilities, and education. People with higher social status are expected to have more suzhi. Bao is the concept of reciprocity. If someone does something good or bad, it should be returned. The reciprocity concept helps to maintain harmony in society. Chinese indigenous psychology might serve as inspiration for researchers from other cultures. Nevertheless, researchers need to pay attention to the risk of the reification of their own cultures. Chinese indigenous psychologists are criticized for overestimating the role of culture on the behavior of Chinese people. Researchers who are developing indigenous psychologies in their cultures should be aware of the political pressure to express the uniqueness of their own culture. In the case of Czech psychology, it is an open question as to whether it should develop its own indigenous psychology or work with researchers from culturally similar nations, like other Slavic cultures.